Формування соціальних інновацій в контексті соціальної відповідальності трудового потенціалу підприємства - Юр'єва, Ірина Анатоліївна; Яцина, Вікторія Валентинівна (Національний технічний університет "Харківський політехнічний інститут", 2021)
Стратегія інновацій в контексті соціальної відповідальності, яку широко застосовують промислові корпорації, передбачає придбання конкурентних переваг за допомогою соціальних інновацій, створення принципово нових товарів або технологій або задоволення існуючих усвідомлених або неусвідомлених потреб новими засобами. Інноваційні системи формуються під впливом безлічі об'єктивно заданих для кожної країни та для кожного підприємства факторів, включаючи їх розміри, наявність ресурсів, в тому числі людського капіталу, особливості історичного розвитку інститутів держави і форм підприємницької діяльності. Серед найбільш значущих досліджень слід виділити такі: вивчення факторів економічного росту, розробка моделей економічної рівноваги, інвестиційна теорія циклу, теорія інвестиційних імпульсів, інституціональна модель конкурентних переваг, різні моделі національної конкурентоспроможності і міжнародного руху капіталів.

The priorities of Ukrainian government policy are the strategic objectives of integrated development of the industrial and social spheres, harmonious and active inclusion in the global and pan-European integration processes in order to provide a high level of social responsibility of the labour potential. The innovation strategy regarding social responsibility, which is widely used by industrial corporations, envisages acquisition of competitive advantages through social innovations, creation of fundamentally new goods and technologies, using new methods to meet existing conscious or unconscious needs. Innovation systems are shaped by many factors that are objectively determined for each country and for each enterprise, including their size, availability of resources, including human capital, historical development of state institutions and forms of entrepreneurship. These factors play a huge role in evolution of innovation activity, including social innovations. The most important studies include studies of economic growth factors, development of economic equilibrium models, investment cycle theory, investment impulse theory, institutional model of competitive advantages, various models of national competitiveness and international capital movement.
Formation social innovation in the context of corporate social responsibility
Keywords: соціальні інновації; трудовий потенціал; соціальна відповідальність; управління; персонал; підприємство; відповідальність; управлінські рішення; керівник; social innovation; innovation; labour potential; social responsibility; management decisions; organisation; partnership